PENERAPAN PENDIDIKAN BAYANI DALAM MENINGKATKAN KEMAMPUAN MENYAMPAIKAN PELAJARAN SISWA SEKOLAH DASAR - Matroni Matroni (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2018)
This study to improve the ability to deliver using Bayani Education in the grade students of SDI Gapura Timur. The subjects of the research are students of Class VI of SDI Gapura Timur with 10 students. The study was conducted in three meetings, with each meeting consisting of planning, action implementation, observation, and descriptions. Technique of data collection is by test, observation, interview, and documentation. The validity of the data using qualitative method of research method focused on existing teaching practices of the archipelago. The author analyzed the learning process that occurred in the SDI Gapura Gapura Timur. The result shows that Bayani education can improve self-learning ability and self- learning of grade 6 students of Gapura Timur.